KORELASI MANAJEMEN SUPERVISI AKADEMIK DAN MOTIVASI BERPRESTASI DENGAN KINERJA GURU - Suryadi Prasetio; Manahan P. Tampubolon; Hotmaulina Sihotang (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2018)
The Correlation Between Management of Academic Supervision, Achievement Motivation with the Teacher’s Performance at PSKD Senior High School Jakarta. This study aims to determine the correlation between management of academic supervision, achievement motivation with the teacher’s performance at PSKD Senior High School Jakarta, with the management of academic supervision as independent variable (X1), achievement motivation (X2) and dependent variabel teacher’s performance (Y). This study was conducted in PSKD Senior High School Jakarta from May to June 2018. The research method is used for correlational research method. Data collection techniques use a questionnaire with Likert scale which measures 1-5. This research is represented by 80 of PSKD Senior High School teachers Jakarta as respondents. The techniques used are a simple correlation analysis, multiple correlation and multiple regression at alpha significance level at 0.05. This study concluded that Hypothesis 1 shows a positive and significant relationship between management of academic supervision and teacher’s performance with a correlation coeficient of ry1 = 0,529, linear regression equation Ŷ = 2,42 + 0,45X1, tcount = 5.51 is greater than ttable = 1,67 and the coefficient of determination r2 = 0,28. Hypothesis 2 shows a positive and significant relationship between achievement motivation and teacher’s performance with a correlation coeficient of ry2 = 0,51, linear regression equation Ŷ = 2,36 + 0,46X2, tcount = 5,20 is greater than ttable = 1,67 and the coefficient of determination r2 = 0,26. Hypothesis 3 shows a positive and significant relationship between management of academic supervision, achievement motivation simultaneously and teacher’s performance with a correlation coeficient of ry12 = 0,65, linear regression equation Ŷ = 1,22 + 0,36X1 + 0,36X2, Fcount = 28,77 is greater than Ftable = 3,12 and the coefficient of determination r2 = 0,41. From the research results it can be concluded that the teacher’s performance at PSKD Senior High School Jakarta can be enchanced by improving the management of academic supervision and achievement motivation.